Applied of image processing technique on semi-auto count of skin spot - Abu Zaki, Anis Izura; Ibrahim, Nabilah; Sari, Suhaila; Mahadi, Lina Farhana (Penerbit Uthm, 2019)
Skin is the biggest organ in the human body and works to separate the inner body part from outer environment. In the skin, there are sebaceous glands found inside the pores of the skin. They are at all over the body except for the palms of the hands and the feet soles. There are more sebaceous glands on the face and scalp than elsewhere. Sebaceous gland secretes an oily protective skin surface, sebum, which is against pathogens and also help to slow down the skin ageing process [1]. They can help to maintain the moisture of the skin. However, the sebaceous glands become overactive sometimes, thus, producing too much sebum and the pores can get clogged together with dead skin [2][3]. This will results in having blackheads along with other factors. Blackhead is one of an acne vulgaris type [4]. It is a small dark spots on the skin that sometimes hard to be seen under a naked eye. If the clogged pores infect the glands, the accumulated sebum may form a sac and slowly increase in size. Lack of sebum production can also provide unsatisfied result that could cause dry skin, which makes the skin, looks rough and dull.